Evaluasi Terhadap Kelancaran Bongkar Muat Pada Gudang CDC Banda PT Multi Terminal Indonesia - Gymnastiar, Muhammad Nanda (Peneliti.net, 2025)
Loading and unloading activities at ports are growing rapidly in line with the increasing need for exports and imports to support economic growth. PT MULTI TERMINAL INDONESIA is one of the companies that provides loading and unloading services for domestic, export and import units in the Tanjung Priok Port area. This research aims to evaluate loading and unloading operations at PT. BKJL at Patimban Harbor. This research was conducted using descriptive qualitative methods. The data collection technique is by conducting interviews and observations. The results of the research show that loading and unloading operations are running well, loading and unloading activities will focus on the Banda CDC Warehouse which is a loading and unloading facility owned by PT MULTI TERMINAL INDONESIA in evaluating loading and unloading activities, so that in the future loading and unloading activities can run more effectively and efficient.